CURRENT SEROPREVALENCE OF LEPTOSPIROSIS AMONG BUFFALOES FROM TAMIL NADU - Balakrishnan, G; Parthiban, M; Meenambighai, TV; Roy, Parimal (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A total of 267 blood samples collected from buffaloes showing clinical signs of anorexia, pyrexia, mastitis, abortion, premature calving and infertility and apparently healthy animals from different districts of Tamil Nadu were subjected to microscopic agglutination test (MAT) to diagnose leptospirosis. The seropositivity to leptospirosis was found to be 75.66% in buffaloes. Out of 12 different serovars screened, only 5 serovars namely australis, ballum, hardjo, hebdomadis and pomona could be observed. The study indicated current circulation of only five leptospiral serovars among buffalo population of Tamil Nadu.
Keywords: Buffaloes; Leptospirosis; Prevalence; Tamil Nadu